Reducing the Transaction Costs of Development Assistance : Ghana’s Multi-Donor Budget Support (MDBS) Experience from 2003 to 2007 - Cavalcanti, Carlos (World Bank, Washington, DC, 2012)
This paper examines whether the structure of the Multi-Donor Budget Support (MDBS) in Ghana evolved over time to minimize transaction costs commonly found in accessing and delivering development assistance in multi-donor settings. While the MDBS was expected to reduce the transaction costs involved in dealing with multiple development agencies, it created three additional sources of transaction costs: coordination failures, the costs of collective action, and measurement costs. The answer that emerges from this paper is that the structure of the MDBS evolved to mitigate these transaction costs. The problems associated with coordination was addressed by delegating the policy dialogue to sector-specific groups aimed at reaching agreements over a narrower set of issues and amongst a smaller group of participants. Also, the MDBS reduced the cost of collective action by devising rules that allowed all the participating agencies to have a role in the decision-making process, and, in doing so, encouraged these agencies to increase the share of their contribution coming through the MDBS, rather than through large projects and off-budget disbursements. There was less success in reaching a settled view on how to reduce so-called measurement costs, however. While the group of development agencies made several attempts to overcome the difficulties in measuring progress in the program supported by the MDBS, it was not able to reach consensus on the extent to which the monitoring of the program should rely on outcome indicators. The Government did not favor the use of outcome indicators, and some development agencies placed greater emphasis on maintaining a dialogue around policy actions aimed at reaching the desired outcomes.